(3GdeNJGQ ef TYQ TYQGA GdCfOdS GdeYGUQjfs - (3Ydj Hf efLH Hf SdjeGf GdcGJH ,CHhGdbGSe GHf GdUjQaj GdeUQj,J (B542 (3g` s ((3YHOGddg YHOGdQMef GdQfhTQj GdCRgQj s)
(3ChdgG (B:s
(3bGd GdTjN CHhGdbGSe GdMeO ddg Ydi SGHZ fYeg GdHdGZI JfbSe Edi fXe hfKQ, hbO GNJda GdfGS aj GdJaVjd HjfgeG s
(3BNQgG (B:s
(3YLHJ def jYJO Ohfc LfI hSgec MJa hGdbVG jahb s
(3ChQGbgG eVWQHI GdJQJjH hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B246 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B698s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B28 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdCOHs